The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.15665/dem.v17i3.1646
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs in México, an approach to their quality of life

Abstract: The objective of the research is to compare the levels of satisfaction between entrepreneurs and subordinates. For the study, data from the Self-Reported Welfare Survey (Biare) of 2014 are used. The work method is a statistical exploration of the data on entrepreneurs. The results suggest that there is no significant difference between the levels of job satisfaction of the two groups. A relevant finding is that entrepreneurs declare less satisfaction with life and with health than subordinates. This may be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Some previous studies also indicated a high quality of life for entrepreneurs compared to representatives of other occupational groups [ 45 – 47 ]. The main reasons for the entrepreneurs' high quality of life include good material situation [ 48 ], opportunity for development [ 46 ] and financial independence [ 49 ]. On the other hand, higher values of the health-related quality of life in the environmental domain in white-collar workers, than in blue-collar workers, were reported by Kowalska et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies also indicated a high quality of life for entrepreneurs compared to representatives of other occupational groups [ 45 – 47 ]. The main reasons for the entrepreneurs' high quality of life include good material situation [ 48 ], opportunity for development [ 46 ] and financial independence [ 49 ]. On the other hand, higher values of the health-related quality of life in the environmental domain in white-collar workers, than in blue-collar workers, were reported by Kowalska et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly important for entrepreneurs, who are often heavily burdened with work and exposed to excessive stress [ 11 ] contributing to occupational burnout [ 12 ], and consequently, to the deterioration of some quality of life indicators [ 13 , 14 ]. This was confirmed by Charles-Leija et al [ 15 ], who showed that entrepreneurs were characterized by lower levels of satisfaction with life and health than their employees. It is also noteworthy that regular PA may indirectly benefit some entrepreneurial qualities such as autonomous motivation [ 16 , 17 ], self-efficacy [ 18 , 19 ], positive social activity [ 20 , 21 ], and high self-assessment [ 22 ].…”
Section: Introductionsupporting
confidence: 55%
“…Some previous studies also indicated a relatively high quality of life for entrepreneurs compared to representatives of other professional groups [4,5,10,11]. Financial advantages [4], possibilities of development [11], and independence [13] are indicated as the main reasons for the high quality of life of entrepreneurs. However, it should be mentioned that Charles-Leija et al [13] reported lower quality of life scores for entrepreneurs compared to their employees.…”
Section: Discussionmentioning
confidence: 83%
“…Financial advantages [4], possibilities of development [11], and independence [13] are indicated as the main reasons for the high quality of life of entrepreneurs. However, it should be mentioned that Charles-Leija et al [13] reported lower quality of life scores for entrepreneurs compared to their employees. The analysis of literature indicates that this may be due to the heavy workload and stress [14] and the difficulty of reconciling professional responsibilities with other areas of life, mainly family life and leisure time [16][17][18]29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation